Perceived exertion and recovery status scores comparisons in professional male soccer players and coaches - Rossi, S.; Eisenman, M.; DeJohn, D.; Phillips, S.; Ryan, G. (The Journal of Strength and Conditioning Research, 2021)
Perceived Recovery Status (PRS) and Rating of Perceived Exertion (RPE) are 2 subjective methods coaches, athletes, and sport scientists have used to quantify training load (TL) and recovery to improve athletic performance. While these values are important to monitor, these tools are more useful if there is an agreement between coaches and players. It is important the prescribed TL matches what the athlete is experiencing during training. Purpose: The intent of this study was to assess subjective measures (PRS and RPE scores) received from athletes and coaches during the course of a 36 weeks competitive season. Methods: PRS scores prior to, and RPE scores after, each practice were collected on 24 professional male soccer players (P) and 2 coaches (C). Athletes were provided a visual of the scale prior to answering each day and each athlete reported their scores away from other athletes and coaches. Coaches were instructed to provide answers to PRS and RPE as to how the players on the team felt. The average of RPE and PRS values from each week (Wk) for both P and C was used for all analyses. Due to the categorical nature of the data, nonparametric Mann-Whitney U Tests were run comparing P to C data for each Wk. Significance was set at p = 0.05. Results: P and C PRS comparisons were significantly different for half of the Wks during the season: Wk9 (median P: 7.0, C: 6.0; p = 0.01), Wk16 (P: 7.0, C: 6.0; p = 0.02); Wk17 (P: 7.0, C: 6.0; p = 0.01); Wk19 (P: 7.0, C: 6.0; p = 0.01); Wk21 (P: 7.0, C: 6.0; p = 0.01); Wk24 (P: 7.0, C: 6.0; p = 0.03); Wk25 (P: 8.0, C: 6.0; p < 0.01); Wk26 (P: 7.0, C: 4.0; p < 0.01); Wk27 (P: 7.0, C: 6.0; p = 0.01); Wk28 (P: 7.0, C: 6.0; p < 0.01); Wk29 (P: 7.0, C: 6.0; p < 0.01); Wk30 (P: 7.0, C: 4.5; p = 0.01); Wk31 (P: 7.0, C: 5.5; p = 0.01); Wk32 (P: 7.0, C: 4.5; p = 0.01); Wk33 (P: 7.0, C: 5.5; p < 0.01); Wk34 (P: 7.0, C: 5.5; p = 0.02); Wk35 (P: 7.0, C: 6.0; p = 0.01) and Wk36 (P: 7.0, C: 6.0; p < 0.01). Average P and C RPE were not significantly different (p > 0.05) for any of the 36 weeks. Conclusions: Results indicate that RPE of practice were similar between P and C throughout the season. C tended to underestimate P self-reported recovery, especially as the season progressed into the latter third of the season. P PRS scores were more consistent throughout the season compared to C. Practical Applications: This is an important consideration for coaching and training staffs when managing athlete TL and recovery. While team averages of PRS and RPE are important, individual P data is also important to track due to individual differences in response to TL. Individual athlete data allows the coaching staff to make specific changes to a specific athlete's recovery plan and future TL.